ISOLATION AND STRUCTURE ELUCIDATION OF IPOLAMIIDE FROM THE STEM BARK OF STACHYTARPHETA ANGUSTIFOLIA MILL VAHL (VERBENACEAE) - M. MOHAMMED; U.M. JAJERE; A. DANMALAM; M. T KOLO; M. BABAKANO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
This research work is aimed at isolating and structural elucidation of the compound from the stem bark extract of S. angustifolia using standard phytochemical and spectroscopic techniques. The grounded powdered material of the stem bark was extracted and partitioned using various solvent of different polarity. Column chromatography, n-BuoH soluble fraction of the ethanol extract of stem bark S. angustifolia was run using silica gel and subsequently pooled fractions from various portions were purified using sephadex LH20 to obtain compound 1. Pure isolate of compound 1 was subjected to analysis using FTIR, 1and 2D NMR. Compound 1 was determined as an Iridoid glucoside Cyclopenta [C] pyran-4-Carboxylic acid, 1-(β-D glucopyranosyloxy)-1, 4A, 5,6,7,7A Hexahydro-4A, 7- dihydroxy-7- methyl-, Methyl Ester, (1S, 4AR,7S, 7AR) (Ipolamiide), MP 218- 220oC, MW C17H27O12, [M]+424(EIMS) on the basis of spectral analysis and Comparism with reference data.